THE CRISIS PHENOMENON IN THE CARE OF PEOPLE WHO USE DRUGS: A PHENOMENOLOGICAL STUDY - Carvalho, Savannah Leitzke; Tisott, Zaira Letícia; Willrich, Janaína Quinzen; Pinho, Leandro Barbosa de; Tomielo, Cláudia Aparecida; Ketzer, Nicole; Nasi, Cintia (Cogitare Enfermagem, 2024)
Objective: To understand the meaning of the crisis phenomenon and the motivations and expectations of workers in the care of people in crisis in a Psychosocial Care Center for Alcohol and Drugs (CAPSad). Method: qualitative research, based on Alfred Schutz’s social phenomenology, was carried out with 14 workers in January and February 2022 in the municipality of Porto Alegre, RS, Brazil. The interviews were subjected to phenomenological analysis. Results: the crisis is reported as a time of suffering, with a potential for transformation, covering subjective, social, and family aspects. Effective crisis care involves verbal management, bonding, and teamwork. The expectations following the care of a person in crisis are aimed at the well-being, reduction of suffering, and protection of the user. Conclusion: It is essential to break away from the biological model in the approach to users, overcoming stigmas and strengthening comprehensive care.